Trust in Science in Light of the Role of Values in Science - Faik Kurtulmuş (Felsefe Arkivi)
The philosophy of science has recently highlighted the ineliminable role of social and ethical values in scientific reasoning, which poses challenges for ensuring trust in science. This article evaluates three approaches to building public trust in science, given the role of values. According to the high epistemic standards approach, scientists should only share results with the public that are highly certain. This paper argues that this approach doesn’t address all types of epistemic risks and can lead to underutilization of scientific findings. The democratic values approach maintains that scientific research should use democratically determined values. This paper argues that, while this approach addresses the shortcomings of the first approach, it also creates difficulties in the international and intertemporal coordination of research and has practical shortcomings. The hybrid approach offered by Boulicault and Schroedercombines elements of the first two approaches with Wilholt’s insights about the role of methodological conventions. However, it fails to combine the benefits of these approaches. The classification of research into discrete categories, essential for executing this approach, also proves to be difficult. The paper concludes that none of these approaches offers a comprehensive solution and highlights the key criteria that an effective solution should fulfill. These criteria include being applicable, fully utilizing scientific knowledge, addressing not just inductive risks but epistemic risks broadly, being aligned with the social organization of science, and being incentive-compatible.